Oxytocin as a protective agent in cisplatin-induced ototoxicity - (:unkn) unknown (SPRINGER, 2016)
Cisplatin is a potent chemotherapeutic drug with serious side effects such as ototoxicity which is characterized by irreversible, bilateral, progressive sensorineural hearing loss. Oxytocin, which is a well-known hormone secreting during pregnancy, has antioxidant and antiinflammatory effect. Our study aims to test and compare the effect of intratympanic (IT) and intraperitoneal (IP) oxytocin on cisplatin ototoxicity with DPOAE. A total of 24 Wistar albino rats were randomly divided into four groups: Group 1 received 0.1-0.3 ml IT saline + IP saline solutions for 4 days (n = 6), Group 2 received cumulative dose of 20 mg/kg IP cisplatin divided into two equal doses in first and second days of experiment + 0.1-0.3 ml IT saline for 4 days, Group 3 received same dose of cisplatin as Group 2 + 0.1-0.3 ml IT oxytocin for 4 days, and Group 4 received same dose of cisplatin as Groups 2 and 3 + IP oxytocin with dose of 1 mg/kg. DPOAE was performed prior to procedure and at the end of the experiment on day 5. Group 2 showed severe ototoxic effect of cisplatin according to DPOAE result (p < 0.05). When compared with Group 2, DPOAE amplitude reductions were smaller in Group 3 (3.2, 3.8, 4.5, 6.3 and 7.6 kHz) (p < 0.05) and Group 4 which is statistically significant in 5.4, 6.3 and 7.6 kHz (p < 0.05). When Group 3 and Group 4 were compared, reductions were smaller in 2.7 and 3.2 kHz in Group 3 (p < 0.05). In this study, we showed the protective effect of IT and IP oxytocin on cisplatin ototoxicity. We suggest oxytocin in cisplatin ototoxicity, especially via IT route even with high-dose cisplatin.
Keywords: Ototoxicity; Cisplatin; Oxytocin; Otoacoustic emission; Intratympanic; Intraperitoneal; INJURY